Lazer, mercado do entretenimento e circuitos futebolísticos nos sertões de Minas Gerais, 1888-1925 - Daniel Venâncio de Oliveira Amaral (2020)
Examining newspapers, census data and works by memorialists, this paper describes and interprets the way in which public or commercial entertainments such as theater, cinema, bars, sports, music concerts and recreational clubs competed at the beginning of the last century for a small expansion of modern public and entertainment societies in the city of Oliveira, Minas Gerais, in a context marked by urban reforms, demographic growth and economic diversification, despite the predominance of general characteristics that are still markedly rural. This paper also sought to understand the historical genesis of body sports, as well as the soccer circuits constituted by intermunicipal meetings, in which sports committees from the West of Minas Gerais, composed mainly of prominent members of the localities, started to fulfill the role of promoting social networks and political cooperation between the partners and the cities involved with the game.